Potential adverse health consequences of climate change related to rheumatic diseases - Thomas Bush (Elsevier, 2021)
There is a growing body of literature regarding the health implications of climate change for the general population, but a scarcity of data specific to patients with rheumatic diseases. Human health will be affected by extreme weather events, heat waves, increased wildfires and a spread in the distribution of vector-borne diseases. Patients with underlying pulmonary, cardiac and renal disease are at high risk for adverse health outcomes related to these events. Many patients with rheumatic diseases share these comorbidities, which would presumably also put them at high risk for poor outcomes. There is research on ambient air pollution that indicates disease flares in patients with systemic lupus erythematosus are linked to elevated particulate matter. These patients are probably also at risk from increased particulate matter emanating from major wildfires. More research is needed on the specific adverse health impacts of climate change on patients with rheumatic diseases in order to guide policy decisions to mitigate the adverse impacts.